2020
DOI: 10.1002/advs.202001266
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Quasi‐van der Waals Ferroelectric Hafnium‐Based Oxide for Integrated High‐Performance Nonvolatile Memory

Abstract: Ferroelectric memories with ultralow-power-consumption are attracting a great deal of interest with the ever-increasing demand for information storage in wearable electronics. However, sufficient scalability, semiconducting compatibility, and robust flexibility of the ferroelectric memories remain great challenges, e.g., owing to Pb-containing materials, oxide electrode, and limited thermal stability. Here, high-performance flexible nonvolatile memories based on ferroelectric Hf 0.5 Zr 0.5 O 2 (HZO) via quasi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 41 publications
(48 reference statements)
1
23
0
Order By: Relevance
“…Among them, atomic layer deposition (ALD) has been frequently used due to its wide industrial coverage. This technique initially results in amorphous hafnia thin films [49,[61][62][63] capped by a metal electrode (usually TiN), and further subjected to rapid thermal annealing to achieve polycrystalline hafnia thin films. [61] The confinement strain during fast annealing suppresses the conventional tetragonal to monoclinic phase transition, resulting in an alternative pathway from tetragonal to orthorhombic phase.…”
Section: Polymorphism Of Hafnia Thin Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, atomic layer deposition (ALD) has been frequently used due to its wide industrial coverage. This technique initially results in amorphous hafnia thin films [49,[61][62][63] capped by a metal electrode (usually TiN), and further subjected to rapid thermal annealing to achieve polycrystalline hafnia thin films. [61] The confinement strain during fast annealing suppresses the conventional tetragonal to monoclinic phase transition, resulting in an alternative pathway from tetragonal to orthorhombic phase.…”
Section: Polymorphism Of Hafnia Thin Filmsmentioning
confidence: 99%
“…[81,105,106] In fact, the wake-up effect is usually accompanied by redistribution of oxygen vacancies and defects in HZO film, which traps charges, pins the domains, and prevents them from switching. [61,107] Thus, it has also been proposed that the wake-up effect can be attributed to the diffusion and redistribution of the oxygen vacancies by repetitive electric field cycling. Kashir et al have investigated the effect of ozone dosage, which influence the defects, on the wake-up of HZO films.…”
Section: Wake-upmentioning
confidence: 99%
“…Because of this, studies on the formation of ferroelectric HfO 2 thin film on PI films have reported poor physical and ferroelectric properties [64,68]. Recently, a mica substrate with high thermal resistance was used for flexible ferroelectric HfO 2 film but had a problem with poor versatility [69]. Therefore, to employ ferroelectric HfO 2 on a flexible device, it will be necessary to introduce a fundamentally low-temperature process.…”
Section: Thermal Annealingmentioning
confidence: 99%
“…The emergence of the Internet of Things (IoT) and artificial intelligence (AI) technology has promoted the rapid development of flexible and stretchable intelligent systems, such as electronic skin (e-skin) (Yang et al, 2019;Wang et al, 2020b), soft robotics (Wang et al, 2018b;Park et al, 2020b), and wearable devices (Liu et al, 2020). In the ideal scenarios, these systems should be able to undergo complex deformations in response to external stimuli, such as bending, twisting, and shearing (Wang et al, 2020c;Wang et al, 2021b;Raeis-Hosseini and Rho, 2021).…”
Section: Introductionmentioning
confidence: 99%